2010
DOI: 10.1111/j.1365-4632.2010.04474.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Ultraviolet radiation and skin cancer

Abstract: Skin cancer is the most common type of cancer in fair-skinned populations in many parts of the world. The incidence, morbidity and mortality rates of skin cancers are increasing and, therefore, pose a significant public health concern. Ultraviolet radiation (UVR) is the major etiologic agent in the development of skin cancers. UVR causes DNA damage and genetic mutations, which subsequently lead to skin cancer. A clearer understanding of UVR is crucial in the prevention of skin cancer. This article reviews UVR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
703
1
65

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 961 publications
(772 citation statements)
references
References 57 publications
3
703
1
65
Order By: Relevance
“…In addition to DNA damage, cell proliferation is a determining factor in mutagenesis and carcinogenesis (3)(4)(5)(6)(7). Skin, in addition to the gastrointestinal epithelium and bone marrow, display relatively high levels of cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to DNA damage, cell proliferation is a determining factor in mutagenesis and carcinogenesis (3)(4)(5)(6)(7). Skin, in addition to the gastrointestinal epithelium and bone marrow, display relatively high levels of cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The main causative agent of skin cancer is the UV component of sunlight. UV radiation (UVR) produces two major lesions in DNA, the cyclobutane pyrimidine dimer (CPD) and the (6-4) photoproduct [(6-4) PP], both of which are mutagenic and carcinogenic in animal model systems and are thought to be the primary cause of skin cancer in humans (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Inflammation is also involved in other UVR-related cutaneous conditions including photosensitivity disorders, photoageing, and skin cancer [119][120][121].…”
Section: Sunburn Responsementioning
confidence: 99%
“…PGE 2 can mediate the initial inflammatory phase but later on it can play a part in the resolution of inflammation and tissue repair [128]; furthermore, continuous production of PGE 2 in unresolved inflammation may contribute to the immune suppression observed in photocarcinogenesis [120]. 12-HETE is a potent leukocyte chemoattract but can also be involved in keratinocyte and fibroblast mediated healing events [31,35], whilst 15-HETE and 13-HODE may assist in restricting pro-inflammatory signals [65,83].…”
Section: Sunburn Responsementioning
confidence: 99%
“…Researchers showed that ultraviolet radiation (UVR) from the solar would be a principal cause of skin melanoma [13,14]. The bigger the UPF worth, the longer a person can stay within the sun until the area of epidermis underneath the material turns into red.…”
Section: Uv-protectionmentioning
confidence: 99%